Diabetes Mellitus and Pregnancy. Perinatal Results in a 3 years Study. - Cristóbal Torres González; Vivian Vázquez Martínez; Joselin Moreno Torres; Angel Rodríguez Cabrera; Amparo Ocampo Sánchez; Ana López Rodríguez del Rey (Medisur)
Background: Diabetes constitutes the most frequent medical complication during pregnancy, and it has a direct impact on the perinatal results. Objectives: To determine the effect of the diabetes on perinatal results. Methods: A descriptive study of series of cases was carried out. Of an universe of 13 603 childbirths from January 1st, 2003 to December 31st, 2005, in the Obstetric Service of the University Hospital ¨Dr. Gustavo Aldereguía Lima¨ in Cienfuegos, a sample of 229 pregnant women with diabetes was taken. Rates were determined for under weight, premature births, congenital malformations, late fetal deaths, macrosomia, asphyxia and assessment of caesarean operation in the diabetic women; as well as the risk of these complications for this group with regard to the non diabetic pregnant women and between the gestational and pre-gestational diabetes. Results: Diabetes incidence and pregnancy was of 1, 68 %. The risk of premature birth (17,4 %), of under weight of the newborn (13,1 %), macrosomia (15,3 %), malformations (3,5 %), neonatal death (0,4 %), late fetal death (0,9 %) and birth by Caesarean operation (64,2 %) was higher in the diabetic population, with regard to the non diabetic. The pre- gestational diabetes turned out to have bigger risks with regard to the gestational one regarding the premature childbirth, the most important congenital malformations and the late fetal deaths. Conclusion: Although the province shows a low incidence of diabetes in the pregnancy, the risk of adverse perinatal results is considerable for this group, especially in pre-gestational diabetic women.